Hierarchies of critical points of a Landau-de Gennes free energy on three-dimensional cuboids. (1st May 2023) - Shi, Baoming; Han, Yucen; Yin, Jianyuan; Majumdar, Apala; Zhang, Lei
Abstract: We investigate critical points of a Landau–de Gennes (LdG) free energy in three-dimensional (3D) cuboids, that model nematic equilibria. We develop a hybrid saddle dynamics-based algorithm to efficiently compute solution landscapes of these 3D systems. Our main results concern (a) the construction of 3D LdG critical points from a database of two-dimensional (2D) LdG critical points and (b) studies of the effects of cross-section size and cuboid height on solution landscapes. In doing so, we discover multiple-layer 3D LdG critical points constructed by stacking 2D critical points on top of each other, novel pathways between distinct energy minima mediated by 3D LdG critical points and novel metastable escaped solutions, all of which can be tuned for tailor-made static and dynamic properties of confined nematic liquid crystal systems in 3D.